MODIFIKASI PATI JAGUNG MELALUI REAKSI OKSIDASI HIDROGEN PEROKSIDA (H2O2) DAN SINAR ULTRAVIOLET-C (UV-C) - Nur Kholifah; Iffah Muflihati; Enny Purwati Nurlaili (Jurnal Pangan dan Gizi, 2018)
Corn starch is widely used by the food processing industries, so it is often found problems caused by the characteristics of the functional properties of natural starches. The aims of this study was to determine the effect of H2O2 and the duration of UV-C lamp on the characteristics of modified corn starch. The research method used with the addition of H2O2 and irradiation with UV-C lamps to modify the original properties of starch. Formulations for modification include H2O2 concentration (0.5, and 0.75%) and duration of UV-C irradiation (5, 10, 15 minutes). Characteristics were determined by analysis of water content, pH, color, total starch, solubility and swelling power. The highest water content (8.18%) was found at 0.5% H2O2 concentration with 15 minutes UV-C irradiation time. The duration of UV-C irradiation can affect the pH value and total starch in corn starch. While the brightness value increases with increasing H2O2 concentration and duration UV-C lamp irradiation. The modification process increased the solubility value, but will reduced the value of swelling power.